Implementasi Pasal 178 Undang-Undang Nomor 23 Tahun 2007 tentang Perkeretaapian : Perspektif Siyasah Tanfidziyyah - Anandita Permata Rahmah (Jurnal Hukum Lex Generalis, 2026)
This study examines the implementation of Article 178 of Law Number 23 of 2007 concerning Railways at PT KAI in Bandar Lampung City from the perspective of siyasah tanfidziyyah. The study is motivated by the continued presence of buildings located within railway-owned land. This condition has led to increased risks of accidents, disruptions to railway operations, and a decline in public safety and order around the railway tracks. This research employs a descriptive qualitative method using interviews, observations, and documentation techniques. The findings indicate that the implementation of the policy has not been optimal, as the community continues to utilize the area for residential and business purposes. PT KAI has the obligation to ensure safety by clearing and sterilizing the area; however, the enforcement process faces obstacles, particularly due to the lack of coordination with local government and law enforcement authorities. From the perspective of siyasah tanfidziyyah, this policy aims to achieve public welfare (maslahah ‘ammah), especially in maintaining public safety, while still considering the principles of social justice and the well-being of affected communities.